The Limits of Design: Explaining Institutional Origins and Change: z wprowadzeniem Boba Jessopa - Pierson, Paul (Journal of Public Governance, 2011)
Political scientists have paid much more attention to the effects of institutions than to issues of institutional origins and change. One result has been a marked tendency to fall back on implicit or explicit functional accounts, in which the effects of institutions explain the presence of those institutions. Institutional effects may indeed provide part of such an explanation. Yet the plausibility of functional accounts depends upon either a set of favorable conditions at the design stage or the presence of environments conducive to learning or competition. Exploring variability in the relevant social contexts makes it possible to both establish the restricted range of functional accounts and specify some promising lines of inquiry into the subject of institutional origins and change.